2021
DOI: 10.3389/fgene.2021.633756
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-Mediated microRNA-375 Upregulation Promotes Progression of Breast Cancer via the Inhibition of FOXO1 and the p53 Signaling Pathway

Abstract: Breast cancer (BC) is the most common gynecologic tumor worldwide where aberrant expression of microRNAs (miRNAs) is frequently involved. Here, we evaluated the function of miR-375 on BC development and the molecules implicated. Differentially expressed genes between tumor and paired normal tissues from BC patients were screened out by microarray analyses. miR-375 was abundantly expressed in BC tissues and cells, and it was correlated with the poor prognosis of patients. Downregulation of miR-375 was introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Also, the authors showed that this miRNA was associated with pathways related to proteoglycans in cancer and focal adhesion 116 . In a different study, the overexpression or miR‐375 through the activation of STAT3 by enhancer of zeste homologue 2 (EZH2) leads the downregulation forkhead box protein O1 and p53, an important antitumor proteins 117 . Interestingly, in a mouse model, Chiba et al 118 observed significantly increased serum levels of miR‐375‐3p after the exposition to radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the authors showed that this miRNA was associated with pathways related to proteoglycans in cancer and focal adhesion 116 . In a different study, the overexpression or miR‐375 through the activation of STAT3 by enhancer of zeste homologue 2 (EZH2) leads the downregulation forkhead box protein O1 and p53, an important antitumor proteins 117 . Interestingly, in a mouse model, Chiba et al 118 observed significantly increased serum levels of miR‐375‐3p after the exposition to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…116 In a different study, the overexpression or miR-375 through the activation of STAT3 by enhancer of zeste homologue 2 (EZH2) leads the downregulation forkhead box protein O1 and p53, an important antitumor proteins. 117 Interestingly, in a mouse model, Chiba et al 118 observed significantly increased serum levels of miR-375-3p after the exposition to radiation. Moreover, miR-375 desensitizes gastric cancer cells to radiation by targeting p53.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that curcumin can inhibit EZH2 (enhancer of zest homolog-2), which is a histone methyltransferase that catalyzes the trimethylation of histone H3 in lys 27 (H3K27me3), is found in an increased amount in human cancer, has an oncogenic, metastatic role, and influences drug resistance. It was postulated that, on the EZH2, miR-375, FOXO1 and p53 axis, special processes with direct impact in the proliferation of the breast tumor could take place [86,87]. Gallardo et al showed, in a study on MCF-10F and MDA-MB-231 cell lines of human breast cancer, that curcumin can modulate the expression of miR-34a and Rho-A, which reduces cancer progression, metastasis, and increases the sensitivity of anti-cancer drugs [88].…”
Section: Breast Cancermentioning
confidence: 99%
“…In recent times, miR-375 has been proved as a tumor-induced regulator in different cancers by activating important regulatory networks. For example, Xin et al demonstrated that overexpression of the miR-375 mediates phosphorylation and methylation of STAT3; also inhibits FOXO1 and p53 axis thereby stimulating the breast cancer progression (15) . Overexpression of circ-0072088 or miR-375 inhibitors promoted hepatocellular carcinoma proliferation, migration, invasion and reduced the cell death by activating JAK2/STAT3 network whereas circ-0072088 downregulation or miR-375 mimics explored opposite function (16) and also miR-375 activated JAK2/STAT3 signaling pathway to inhibit stemness of the breast cancer (17) .…”
Section: Introductionmentioning
confidence: 99%
“…Alam et al found that MiR-375 regulates cell growth, proliferation, cell migration, and apoptosis by modulating the CTGF-EGFR-PIK3CA-AKT signaling axis in human colorectal cancer cells (18) . Furthermore, several investigations were demonstrated that constitutive expression of miR-375 promotes oncogenicity in the breast (19)(20)(21)(22)(23) , prostate (24)(25)(26)(27) , and lung cancer (28) . In addition, few pieces of literature reported that miR-375 functions as a tumor suppressor (16,(29)(30)(31) .…”
Section: Introductionmentioning
confidence: 99%